Analysis Of The Implementation Of Certification Policy In Improving The Competence Of Elementary School Teachers In Poso District, North City, Poso Regency - Rusli, Moh (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2026)
Studies This analyze Implementation Policy Certification In Increase Competence of Teaching Staff Elementary Schools in the District North Poso City Regency Poso With use approach studies case qualitative through interview in-depth , observation field , and analysis documents , findings show that For Source Power human and infrastructure available but need improvement in skills whereas disposition and structure bureaucracy can categorized walk Enough Good whereas For communication walk not enough good . In terms of overall , implementation Policy Certification In Increase Competence of Teaching Staff Elementary Schools in the District North Poso City Regency Poso can categorized walk Enough good . Study This recommend to maximize management certification for school teachers base in the District North Poso City is needed especially socialization funds to schools